Impact of incident myocardial infarction on the risk of venous thromboembolism: the Tromsø Study. (10th May 2016) - Rinde, L. B.; Lind, C.; Småbrekke, B.; Njølstad, I.; Mathiesen, E. B.; Wilsgaard, T.; Løchen, M.‐L.; Hald, E. M.; Vik, A.; Brækkan, S. K.; Hansen, J.‐B.
Abstract : Essentials Registry‐based studies indicate a link between arterial‐ and venous thromboembolism (VTE). We studied this association in a cohort with confounder information and validated outcomes. Myocardial infarction (MI) was associated with a 4.8‐fold increased short‐term risk of VTE. MI was associated with a transient increased risk of VTE, and pulmonary embolism in particular. Summary: Background: Recent studies have demonstrated an association between venous thromboembolism (VTE) and arterial thrombotic diseases. Objectives: To study the association between incident myocardial infarction (MI) and VTE in a prospective population‐based cohort. Methods: Study participants ( n  = 29 506) were recruited from three surveys of the Tromsø Study (conducted in 1994–1995, 2001–2002, and 2007–2008) and followed up to 2010. All incident MI and VTE events during follow‐up were recorded. Cox regression models with age as the time scale and MI as a time‐dependent variable were used to calculate hazard ratios (HRs) of VTE adjusted for sex, body mass index, blood pressure, diabetes mellitus, HDL cholesterol, smoking, physical activity, and education level. Results: During a median follow‐up of 15.7 years, 1853 participants experienced an MI and 699 experienced a VTE. MI was associated with a 51% increased risk of VTE (HR 1.51; 95% confidence interval [CI] 1.08–2.10) and a 72% increased risk of pulmonary embolism (PE) (HR 1.72; 95% CI 1.07–2.75), but not significantly associated with the risk of deep vein thrombosis (DVT) (HR 1.36; 95% CI 0.86–2.15). The highest risk estimates for PE were observed during the first 6 months after the MI (HR 8.49; 95% CI 4.00–18.77). MI explained 6.2% of the PEs in the population (population attributable risk) and 78.5% of the PE risk in MI patients (attributable risk). Conclusions: Our findings indicate that MI is associated with a transient increased VTE risk, independently of traditional atherosclerotic risk factors. The risk estimates were particularly high for PE.